Nonadherence and unsuppressed viral load across adolescence among US youth with perinatally acquired HIV. (1st October 2019) - Kacanek, Deborah; Huo, Yanling; Malee, Kathleen; Mellins, Claude A.; Smith, Renee; Garvie, Patricia A.; Tassiopoulos, Katherine; Lee, Sonia; Berman, Claire A.; Paul, Mary; Puga, Ana; Allison, Susannah
Abstract : Objective: To identify factors associated with nonadherence and unsuppressed viral load across adolescence among youth with perinatally acquired HIV. Design: Longitudinal study at 15 US clinical sites. Methods: Self-reported antiretroviral medication nonadherence (any missed dose, past week) and unsuppressed viral load (HIV RNA > 400 copies/ml) were assessed annually. Individual, caregiver, social, and structural factors associated with nonadherence and unsuppressed viral load were identified by age (years): 8–11 (preadolescence), 12–14 (early adolescence), 15–17 (middle adolescence), and 18–22 (late adolescence/young adulthood), utilizing multivariable generalized linear mixed effects models. Results: During a median 3.3-year follow-up, 381 youth with perinatally acquired HIV contributed viral load measurements and 379 completed 1190 adherence evaluations. From preadolescence to late adolescence/young adulthood, prevalence of nonadherence increased from 31 to 50% ( P  < 0.001); prevalence of unsuppressed viral load increased from 16 to 40% ( P  < 0.001). In adjusted analyses, in pre, middle, and late adolescence/young adulthood, perceived antiretroviral side effects were associated with nonadherence. Additional factors associated with nonadherence included: in preadolescence, using a buddy system (as an adherence reminder); in early adolescence, identifying as black, using buddy system; in middle adolescence, CD4 + % less than 15%, unmarried caregiver, indirect exposure to violence, stigma/fear of inadvertent disclosure, stressful life events. Associations with unsuppressed viral load included: in early adolescence, youth unawareness of HIV status, lower income; in middle adolescence, perceived antiretroviral side effects, lower income; in late adolescence/young adulthood, distressing physical symptoms, and perceived antiretroviral side effects. Conclusion: Prevalence of nonadherence and unsuppressed viral load increased with age. Associated factors varied across adolescence. Recognition of age-specific factors is important when considering strategies to support adherence. Abstract : Supplemental Digital Content is available in the text